The conditional impact of trade openness on economic growth in ASEAN: Governance, ICT, human capital, and natural resources as moderators - Nguyen, Thanh Thi; Nguyen, Tinh Thi (International Journal of Innovative Research and Scientific Studies, 2025)
This study investigates the conditional impact of trade openness on economic growth in ASEAN countries over the period 2000–2023, employing advanced panel data econometrics. The main estimation technique used is the Prais-Winsten regression with Panel-Corrected Standard Errors (PCSE), which effectively addresses the issue of cross-sectional dependence an inherent challenge in regional panel datasets due to economic interlinkages among countries. To ensure the robustness of the findings and to address potential endogeneity, the study further applies the Instrumental Variables Two-Stage Least Squares (IV-2SLS) estimation technique. The empirical results reveal that trade openness has a significantly positive effect on economic growth only when accompanied by strong governance, high information and communication technology (ICT) penetration, and robust human capital. Conversely, the growth benefits of trade openness are weakened or even reversed in countries with high dependence on natural resources, aligning with the resource curse hypothesis. These findings highlight the importance of complementary structural policies, including institutional strengthening, digital and educational investment, and economic diversification to maximize the developmental gains from trade liberalization in ASEAN.